Pemahaman Auditor dalam Audit Konstruksi Jalan: Analisis Hukum Normatif - Baren Sipayung; Andi Wahyudi; Doan H. Tambun (Jurnal Supremasi, 2023)
This research discusses the auditor's responsibility in understanding the examination criteria and assessment standards, especially in construction audits, as well as the importance of complying with the guidelines set by the Ministry of Public Works and Public Housing (PUPR) regarding road construction audits. The normative legal research reveals that the PUPR Ministry has issued Circular Letter Number: 02/SE/Db/2018 on the 2018 Bina Marga General Specifications for Road and Bridge Works, which was later revised with Circular Letter Number: 16.1/SE/Db/2019 in October 2020. Government contractors must comply with the rules issued by the government as a condition for the validity of the agreement, even though it is not in the form of legislation. In construction inspection by the Supreme Audit Agency (BPK), the main concern is on quantity testing of thickness, length, and width. Good communication with suppliers, supervisory consultants, and the government is very important in the measurement and payment methods of construction work to avoid overpayments that can harm the state or region due to volume deficiencies in physical inspection. The results of this study provide a foundation for auditors and the government to understand the importance of complying with applicable guidelines and rules in road construction audits.